Rancang Bangun Mesin CNC Router Mini Untuk Pembelajaran Mahasiswa Jurusan Teknik Mesin - Abdul Salam; Muhammad Iswar; Muhammad Rifaldi; Sumantri Malik; Kurniawan Putra (Jurnal Teknik Mesin Sinergi, 2019)
The aims of this research are accelerate finishing time and improve the accuracy of manufacture of the engraved contour products on work pieces such as soft metals, acrylics, and wood. Methods of these researches were designed, manufacture, and experimented based on work of the machine. Components of the mini CNC router machine are designed by autodesk inventor software, its dimensions 60 x 60 cm. Furthermore, the calculation and selection of materials, manufacture of machine components, calibrated by mach3mill software and testing the performance of the engine in the three-axis movement mode; manual mode, MDI, and automatic third axis X, Y, and Z using the NC program. The results obtained show the accuracy and precision of the three X, Y and Z axis trajectories according to the permissible tolerance values, 0.01 mm, 0.01 mm and 0.05 mm respectively. The suitability of the program made and the machining results on the contour of the workpiece engraving do not show significant deviations, 0.1 mm for the X and Y axis, and 0.3 mm for the Z axis. Making engraving products on workpieces by using a CNC Router machine is faster and more efficient than manual manufacturing. Research output of this CNC router machine will be used in the practicum jobs for the NC basic programming practice course